THE INFLUENCE OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE ON COMPANY VALUE WITH PROFIT MANAGEMENT AS MODERATING VARIABLES - Liza Widya Hasyim (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This research aims to determine the influence of good corporate governance (institutional ownership, managerial ownership, independent board of commissioners and audit committee) on company value in property & real estate sector companies on the Indonesia Stock Exchange. Apart from that, this research also aims to find out whether earnings management can be used as a moderating variable in the model. The research design carried out was causal relationship research with a quantitative approach. The sample in this research is 26 property & real estate companies listed on the IDX from 2016 to 2022. The type of data used in this research is secondary data. The sampling technique uses purposive sampling. And the data analysis technique uses multiple linear regression analysis and interaction testing (moderating) which is carried out with the help of Eviews 9 software. The results of this research show that partially institutional ownership, independent board of commissioners and audit committee have a positive and significant influence on company value. As well as other results which show that earnings management is not a moderating variable in the influence of institutional ownership, managerial ownership, independent board of commissioners and audit committee on company value in property & real estate sector companies listed on the Indonesia Stock Exchange